Permissive role of AMPK and autophagy in adiponectin deficiency-accentuated myocardial injury and inflammation in endotoxemia. (April 2016) - Ren, Jun; Xu, Xihui; Wang, Qiurong; Ren, Sidney Y.; Dong, Maolong; Zhang, Yingmei
Abstract: Background: Adiponectin (APN), an adipose-derived adipokine, alleviates lipopolysaccharide (LPS)-induced injury in multiple organs including hearts although the underlying mechanism in endotoxemia remains elusive. This study was designed to examine the role of adiponectin in LPS-induced cardiac anomalies and inflammation as well as the underlying mechanism with a focus on autophagy — a conserved machinery for bulk degradation of intracellular components. Methods and results: Wild-type (WT) and APN −/− mice were challenged with LPS (4 mg/kg) or saline for 6 h. Echocardiography, cardiomyocyte contractile and intracellular Ca 2 + properties were evaluated. Markers of autophagy, apoptosis and inflammation including LC3B, p62, Beclin1, AMPK, mTOR, ULK, Caspase 3, Bcl-2, Bax, TLR4, TRAF6, MyD88, IL-1B, TNFα, HMGB1, JNK and IκB were examined using Western blot or RT-PCR. Our results showed that LPS challenge reduced fractional shortening, compromised cardiomyocyte contractile capacity, intracellular Ca 2 + handling properties, apoptosis and inflammation, which were accentuated by adiponectin ablation. Adiponectin ablation unmasked the LPS-induced cardiac remodeling (left ventricular end systolic diameter) and prolongation of cell shortening. The detrimental effects of adiponectin ablation were associated with dampened autophagy in response to LPS through an AMPK-mTOR-ULK1-dependent mechanism. In vivo administration of AMPK activator AICAR or the autophagy inducer rapamycin effectively attenuated or obliterated LPS-induced and adiponectin deficiency-accentuated responses without affecting TLR4, TRAF6 and MyD88. Conclusions: The findings suggest that AMPK and autophagy may play a permissive role in the adiponectin deficiency-exacerbated cardiac dysfunction, apoptosis and inflammation under LPS challenge possibly at the post-TLR4 receptor level. Highlights: Adiponectin deficiency exacerbates LPS-induced myocardial injury. Adiponectin deficiency lessens LPS-induced autophagy and AMPK activation. Activation of AMPK and autophagy rescue LPS-induced cardiac inflammation. Activation of AMPK and autophagy rescue LPS-induced cardiac mechanical defect.